Developing Students’ Entrepreneurial Character Through the Market Day Program Towards Schools with an Entrepreneurial Culture: Pengembangan Karakter Entrepreneur Siswa Melalui Program Market Day Menuju Sekolah dengan Budaya Wirausaha - Firdaus, Rizal; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2026)
Abstract: General Background: Entrepreneurship education in elementary schools provides a foundation for developing independence, creativity, responsibility, and courage. Specific Background: The Market Day program at MI Muhammadiyah Citanggulun provides students with practical experience in designing, producing, marketing, and selling products. Knowledge Gap: Previous studies have provided limited explanations of comprehensive Market Day implementation in character-based elementary education, including teacher-parent roles and Pancasila Student Profile Project integration. Aims: This study explores strategies for developing students’ entrepreneurial character through Market Day. Results: Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. Findings indicate development of independence, responsibility, creativity, courage, leadership, collaboration, and social awareness through practical activities. Novelty: The study combines Market Day practice, school-family collaboration, and Pancasila Student Profile Project integration. Implications: Sustainable collaboration among teachers, parents, and students can support Market Day as part of an entrepreneurial school culture. Key Findings Highlights Students developed independence, responsibility, creativity, and courage through practical activities. Teacher and parent collaboration supported students’ entrepreneurial character development. Integration with Pancasila Student Profile Project supported a sustainable school culture. Keywords : Entrepreneurial character, Market Day, Elementary education, School-Family Collaboration, Pancasila Student Profile Project